Performance of Bamboo based Agri-silvicultural Systems in North Odisha, India - Behera, Suryakanta; Mahapatra, A. K.; Mishra, P. J.; Pattanayak, S.; Panda, D. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted at Gobardhansul village of Baripada block, Mayurbhanj, during Kharif season of June, 2014 to study the performance of bamboo based agri-silvicultural systems in north Odisha. The silvicultural component Bambusa Vulgaris was grown at three different spacings (5×5 m2, 8×5 m2 and 8×8 m2) and four intercrops (cowpea, rice bean, turmeric and yam) were taken up within the interspaces in a randomized block design with 3 replications. Cowpea (Var: Utkalmanika), rice bean (var: SRBS-35), turmeric (var. Surama) and yam (var: Orissa Elite) were sown on 2nd July 2014 with recommended agronomic management practices and received 963.4 mm rainfall during the growing season. Maximum clump height, clump girth, total numbers of culms/clump and canopy diameter were recorded in bamboo at 8×8 m2 spacing followed by 8×5 m2 spacing. The narrowest spacing of 5×5 m2 had the lowest values of all growth parameters during the period of study. Irrespective of the spacing, cowpea and rice bean intercropped with bamboo recorded significantly more growth of bamboo as compared to turmeric and yam. All the intercrops yielded maximum at wider spacing and yield decreased progressively with decrease in spacing from 8×8 m2 to 5×5 m2. The decrease in bamboo yield obtained from 8×8 m2 spacing was to the extent of 15.57 and 6.80%, respectively over the narrower spacing of 5×5 m2 and 8×5 m2.